Catalogus der Bibliotheek van de Vereeniging ter Bevordering van de Belangen des Boekhandels te Amsterdam, Vol. VII - Brouwer, G.J.,; Vries, Anne Gerard Christiaan de, (Catalogus der Bibliotheek van de Vereeniging ter Bevordering van de Belangen des Boekhandels te Amsterdam ;, 1965)
This volume lists all New Acquisitions 1949-1964 of publications in the field of History of the book, Bibliography, History of typography, and allied subjects. Articles from periodicals, yearbooks, etc. are also included. Fully indexed.